Reactive Oxygen Species in Plants: Their Generation, Signal Transduction, and Scavenging Mechanisms - Thirupathi Karuppanapandian; Jun-Cheol Moon; Changsoo Kim; Kumariah Manoharan; Wook Kim (Australian Journal of Crop Science, 2011)
Reactive oxygen species (ROS) are a by-product of normal cell metabolism in plants; however, under stress conditions, the balance between production and elimination is disturbed. ROS rapidly inactivate enzymes, damage vital cellular organelles in plants, and destroy membranes by inducing the degradation of pigments, proteins, lipids and nucleic acids which ultimately results in cell death. In addition to degrading macromolecules, ROS act as a diffusible signal in signal transduction pathways and also as a secondary messenger in various developmental pathways in plants. Plants possess a complex battery of enzymatic and non-enzymatic antioxidative defense systems that can protect cells from oxidative damage and scavenge harmful ROS that are produced in excess of those normally required for various metabolic reactions. The mechanism by which ROS is generated in aerobic organisms is poorly understood. This review paper describes the generation, origin, and role of ROS in signal transduction and cell death, and the removal of ROS by antioxidative defense systems in plants during various developmental pathways.